Structural and geochronological studies on the Liba goldfield of the West Qinling Orogen, Central China - Zeng, Qing-Tao; McCuaig, T; Hart, Craig; Jourdan, Fred; Muhling, Janet; Bagas, Leon (Springer, 2012)
The Liba goldfield, located to the northeast of the Zhongchuan Granite in the West Qinling Orogen (WQO) of mainland China, contains the largest known gold resource of 2.8 Moz in the Zhongchuan area. Devonian metasedimentary rocks host the structurally controlled gold mineralization, which is associated with silica–sericite–chlorite–carbonate alteration. Two major styles of mineralization occurred at the goldfield, which are disseminated sediment-hosted and quartz vein hosted types. Pyrite, arsenopyrite, and arsenian pyrite are major gold carriers and gold also occurs as native gold grains and electrum spatially associated with the sulfides. Numerous felsic/intermediate dykes have a similar structural control as the mineralization, and their contacts with host rocks are recognized as favorable zones for mineralization. Detailed fieldwork in conjunction with geochronological studies has helped to define the deformation history and gold metallogenesis of the goldfield. Three major phases of deformation have been recognized in the Zhongchuan area. The first deformation (D1) event was compressional in broadly a N–S orientation, the second (D2) event was also compressional and orientated in a NE–SW direction, and the third (D3) event was post-mineralization and was associated with the emplacement of barren calcite and anhydrite veins. Compression related to D2 is the key process that controlled the distribution of igneous dykes and gold mineralization in the Liba goldfield. Both igneous and hydrothermal fluids preferentially focused along dilational jogs under local trans-extension, which took place during the late stage of D2.Precise dating with high-resolution ion microprobe (SHRIMP) U–Pb on zircon and 40Ar/39Ar on muscovite, biotite, hornblende, and plagioclase of crosscutting pre-mineralization granitic porphyry and diorite dykes have constrained the mineralization age to after ca. 227 Ma. 40Ar/39Ar analysis of minerals formed in hydrothermal alteration zones associated with gold mineralization indicates that there was a widespread ca. 216 Ma hydrothermal event that affected almost all lithologies in the area. This detailed investigation is the first study to tightly constrain the timing of gold mineralization in the WQO. The broadly overlapping timing and similar structural control of the mineralization and igneous dykes show a promising correlation, which could be potentially used to map this Late Triassic gold mineralization event in the WQO.